Is it the right time now to replace the diesel system with the natural gas system at Al Duqm in the Sultanate of Oman?. Issue 1 (31st December 2022) - Abdul-Wahab, Sabah; Charabi, Yassine; Al-Mahruqi, Abdul Majeed; Osman, Isra
Abstract : Al Duqm is going through the huge development of its industrial and tourism sectors. As Al Duqm's demand for energy grows, the need for reliable, secure, efficient, cost-effective, and low polluting energy supply is also increasing. Al Duqm's current mode of electrification (diesel) does not satisfy this need. This study was conducted to test the possibility of using natural gas to electrify Al Duqm. The researchers compared diesel and natural gas to satisfy an electrical load demand as high as 175, 000 kW. The results indicated that the use of natural gas instead of diesel generators would save about USD 0.2027/kWh on the cost of electricity, USD 227 million/year on operating costs, and USD 30 million on initial capital. Moreover, using a natural gas generator will avoid generating 186, 478, 827 kg/year of pollutants. Thus, using natural gas generators for energy generation is more effective in terms of both economics and the environment. Highlights The use of natural gas instead of diesel will save some of the electricity costs. The use of natural gas will eliminate the generation of SO2 . The use of natural gas will reduce the emission of CO2 .